B cell-T cell interplay in immune regulation: A focus on follicular regulatory T and regulatory B cell functions - Tan, Diaoyi; Yin, Wei; Guan, Fei; Zeng, Wanjiang; Lee, Pamela; Candotti, Fabio; James, Louisa K; Saraiva Camara, Niels Olsen; Haeryfar, S.M. Mansour; Chen, Yan; Benlagha, Kamel; Shi, Lewis Zhichang; et al. (Frontiers in Cell and Developmental Biology, 2022)
B cells are the core components of humoral immunity. A mature B cell can serve in multiple capacities, including antibody production, antigen presentation, and regulatory functions. Forkhead box P3 (FoxP3)-expressing regulatory T cells (Tregs) are key players in sustaining immune tolerance and keeping inflammation in check. Mounting evidence suggests complex communications between B cells and Tregs. In this review, we summarize the yin-yang regulatory relationships between B cells and Tregs mainly from the respective of T follicular regulatory (Tfr) cells and regulatory B cells (Bregs). We discuss the regulatory effects of Tfr cells on B cell proliferation and the germinal center response. Additionally, we review the indispensable role of B cells in ensuring homeostatic Treg survival and describe the function of IL-10+ regulatory B cells (Bregs) in promoting Treg responses. Finally, we introduce a new subset of Tregs, termed Treg-of-B cells, which are induced by B cells, lake the expression of FoxP3 but still own immunomodulatory effects. In this article, we also enumerate a sequence of research from clinical patient and experimental models to clarify the role of Tfr cells to germinal centers and the role of convention B cells and Bregs to Tregs in the context of different diseases. This review provides an updated overview of immunoregulatory networks and unveils potential targets for therapeutic interventions against cancer, autoimmune diseases and allograft rejection.